An organic salt capable of inhibiting side reactions such as dendrites and corrosion as an electrolyte for aqueous zinc ion batteries

By introducing organic salt additives in the electrolytes of zinc ion batteries in the water system, such as sodium sodium or sodium citrate, the problem of poor stability during the charging and discharge process of batteries is solved, and the suppression of side reactions such as chief crystals and corrosion is achieved, which improves the side effects of corrosion and improves. The cycle stability and electrochemical performance of the battery.

CN114824511BActive Publication Date: 2025-01-28ANHUI UNIV

Patent Information

Application Number
CN202210474843.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-29
Publication Date
2025-01-28
Estimated Expiration
2042-04-29

AI Technical Summary

Technical Problem

Water-based zinc ion batteries have poor stability during charging and discharge, and are prone to side reactions such as dendrites' growth and corrosion, which affect the service life and electrochemical performance of the battery.

Method used

By introducing organic salt additives in the electrolyte, such as sodium sodium liquan acid or sodium citrate, adsorb on the surface of zinc, regulate the sedimentation site and deposition method of zinc ions, reduce the activity and quantity of active water, thereby suppressing the vice of chiefs and corrosion of corrosion reaction.

Benefits of technology

Effectively suppress the side reactions such as Zhi crystal and corrosion, improve the cycle stability and electrochemical performance of the zinc -ion battery of the water system, extend the service life of the battery, and reduce the production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114824511B_ABST
    Figure CN114824511B_ABST
Patent Text Reader

Abstract

The present invention discloses an organic salt capable of inhibiting side reactions such as dendrites and corrosion as an aqueous zinc ion battery electrolyte, wherein the aqueous zinc ion battery electrolyte comprises a zinc salt, deionized water and an organic salt additive; the zinc salt is zinc sulfate; and the organic salt additive is sodium tartrate or sodium citrate. The organic salt additive provided by the present invention can be adsorbed on the surface of zinc in the electrolyte, improve the interface environment between the zinc negative electrode and the electrolyte, and destroy the original solvation shell of the zinc ion, thereby inhibiting the occurrence of side reactions such as dendrites and corrosion, and ultimately extending the service life of the aqueous zinc ion battery and improving the cycle stability. In addition, the additive provided by the present invention has a wide range of sources and low cost, and the preparation method is green and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aqueous zinc ion batteries, and in particular relates to an aqueous zinc ion battery electrolyte capable of inhibiting side reactions such as dendrites and corrosion, and an application thereof. Background Art

[0002] The exploitation and utilization of traditional resources such as oil and coal has seriously polluted our environment and increased the amount of CO in the atmosphere. 2 Our increasing concern for the environment and the requirement to reduce greenhouse gas emissions have prompted the development and use of renewable energy sources such as solar and wind power. However, these renewable energy sources are only available intermittently. Therefore, rechargeable batteries are considered to be the preferred energy storage solution for the next generation of sustainable energy providers, which can store the energy generated by these intermittent energy sources.

[0003] Lithium-ion batteries (LIBs) are the most widely studied rechargeable batteries and are used in large-scale energy storage equipment, new energy vehicles and other fields. However, the organic electrolytes used in LIBs bring huge safety risks to people's use, such as being flammable and explosive, toxic and volatile. In addition, the economic cost of LIBs is relatively high, and the assembly process is cumbersome and complex, requiring extremely strict environmental conditions. Therefore, designing a low-cost, high-safety water-based battery system is an urgent need to solve many of these problems.

[0004] Compared with other active metals (lithium, sodium, potassium), zinc has better tolerance to oxygen and humid atmosphere. Due to its inherent characteristics, it can be used directly as a stable negative electrode, which greatly simplifies the battery configuration and reduces the processing and assembly costs. Not only that, the zinc negative electrode also has a high theoretical capacity (820mAh / g) and a low redox potential (-0.76V vs.SHE). However, aqueous zinc-ion batteries have poor stability during charging and discharging, and problems such as dendrite growth and the generation of by-products will occur during the cycle process. Summary of the invention

[0005] In view of the problems existing in the above-mentioned prior art, the present invention provides an aqueous zinc ion battery electrolyte and its application which can inhibit side reactions such as dendrites and corrosion, aiming to inhibit side reactions such as dendrites and corrosion, improve the electrochemical performance of the battery, and extend the service life of the battery.

[0006] The present invention improves the environment of the zinc negative electrode in the electrolyte by optimizing the electrolyte, and the most common means of optimizing the electrolyte is to introduce an electrolyte additive. Here, we use an organic salt additive (sodium tartrate or sodium citrate) as an electrolyte additive for an aqueous zinc ion battery. Tartrate ions or citrate ions can be adsorbed on the surface of the zinc sheet, adjust the deposition site and deposition mode of the zinc ions, and achieve uniform deposition of zinc ions on the surface of the zinc foil. And tartrate ions or citrate ions can replace the active water molecules in the original solvation layer of the zinc ions, so that the activity of the active water molecules is reduced and the number is reduced. Therefore, the organic salt additive (sodium tartrate or sodium citrate) can inhibit side reactions such as dendrites and corrosion, which helps to extend the service life of the aqueous zinc ion battery and improve the electrochemical performance. In addition, sodium tartrate and sodium citrate are cheap and green, which is of great significance for building a high-performance and low-cost aqueous zinc ion battery.

[0007] The invention discloses an aqueous zinc ion battery electrolyte capable of inhibiting side reactions such as dendrites and corrosion, and comprises zinc salt, deionized water and an organic salt additive.

[0008] The zinc salt is zinc sulfate; the organic salt additive is sodium tartrate or sodium citrate.

[0009] Furthermore, the concentration of the organic salt additive in the aqueous zinc ion battery electrolyte is 0.01 to 0.03 mol / L.

[0010] The method for preparing the aqueous zinc ion battery electrolyte comprises first dissolving zinc sulfate particles with deionized water, then taking an organic salt additive and adding it to the zinc sulfate solution, and finally stirring the solution to mix it evenly, thereby obtaining a zinc sulfate electrolyte containing the organic salt additive. Specifically, the method comprises the following steps:

[0011] Step 1: Weigh 2.876 g to 2.880 g of zinc sulfate (ZnSO 4 ) in a beaker, add a little deionized water to dissolve; then weigh the organic salt additive (sodium tartrate or sodium citrate) particles in a beaker, add deionized water to the 10mL mark, stir while adding, so that the particles are completely dissolved; after dissolution, continue to stir (magnetic stirring for 6 to 10 hours) to mix evenly;

[0012] Step 2: The solution obtained by sufficient stirring is filtered by suction through a microporous filter membrane to remove insoluble impurities.

[0013] In step 1, the amount of sodium tartrate organic salt added is 0.023-0.069 g, and the amount of sodium citrate organic salt added is 0.030-0.089 g, thereby obtaining an electrolyte with an organic salt concentration of 0.01-0.03 mol / L.

[0014] The application of the aqueous zinc ion battery electrolyte of the present invention is to construct an aqueous zinc ion battery with the aqueous zinc ion battery electrolyte. The aqueous zinc ion battery comprises a positive electrode, a negative electrode, a diaphragm and the aqueous zinc ion battery electrolyte.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0016] 1. The electrolyte additive of the present invention adopts conventional medicines, and the preparation method is simple and environmentally friendly. It can be obtained by a simple dissolution method and then applied in aqueous zinc ion battery electrolyte.

[0017] 2. The organic salt of the present invention, through the synergistic effect of adsorption and solvation, the anions in the organic salt will first be adsorbed on the zinc surface to adjust the interface environment between the zinc negative electrode and the electrolyte. 2+ Combined with Zn 2+ The coordinated active water reduces the activity. These two synergistic effects jointly inhibit side reactions such as zinc dendrites and corrosion in aqueous zinc ion batteries.

[0018] 3. The cycle stability of the zinc ion battery using the organic salt additive of the present invention is significantly improved, showing more excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a long cycle comparison diagram of a symmetrical zinc battery using an electrolyte containing different concentrations of sodium tartrate additives in Example 1 and an electrolyte without the additive;

[0020] Figure 2 This is a comparison chart of the long cycle of a symmetrical zinc battery using the electrolyte containing different concentrations of sodium citrate additive in Example 2 and the electrolyte without additive;

[0021] Figure 3 The figure is a comparison chart of the coulombic efficiency of Zn-Cu batteries using the electrolyte containing different concentrations of sodium tartrate additive in Example 1 and the electrolyte without additive;

[0022] Figure 4 The figure is a comparison chart of the coulombic efficiency of Zn-Cu batteries using the electrolyte containing different concentrations of sodium citrate additive in Example 2 and the electrolyte without additive;

[0023] Figure 5 XRD comparison diagram of zinc sheets after battery cycles using the electrolyte containing organic salt additives in Example 1 and Example 2 and the electrolyte without additives;

[0024] Figure 6 is a scanned image of a zinc foil after battery cycling using the electrolyte without an organic salt additive in Example 1;

[0025] Figure 7 This is a scanned image of a zinc foil after battery cycling using the electrolyte containing the sodium tartrate organic salt additive in Example 1;

[0026] Figure 8 This is a scan of the zinc foil after the battery cycle using the electrolyte containing the sodium citrate organic salt additive in Example 2;

[0027] Fig. 9 XRD comparison diagram of zinc foil after being immersed in the electrolyte containing organic salt additives in Example 1 and Example 2 and the electrolyte without additives for 7 days;

[0028] Fig.10 This is a scanned image of a zinc foil after being immersed in the electrolyte without an organic salt additive in Example 1 for 7 days;

[0029] Fig.11 This is a scanned image of a zinc foil after being immersed in the electrolyte containing the sodium tartrate organic salt additive in Example 1 for 7 days;

[0030] Fig.12 This is a scanned image of a zinc foil after being immersed in the electrolyte containing the sodium citrate organic salt additive in Example 2 for 7 days;

[0031] Fig.13 The figure is a comparison of the rate performance of aqueous zinc ion batteries using the electrolyte containing the sodium tartrate additive in Example 1 and the electrolyte without the additive;

[0032] Fig.14 The figure is a comparison of the rate performance of aqueous zinc ion batteries using the electrolyte containing sodium citrate additive and the electrolyte without additive in Example 2;

[0033] Fig.15 The figure is a comparison of the cycle performance of aqueous zinc ion batteries using the electrolyte containing sodium tartrate additive and the electrolyte without additive in Example 1;

[0034] Fig.16 The figure is a comparison chart of the cycle performance of aqueous zinc ion batteries using the electrolyte containing sodium citrate additive in Example 2 and the electrolyte without additive. DETAILED DESCRIPTION

[0035] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0036] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0037] Unless otherwise specified, the reagents and materials used in the following examples can be obtained from commercial sources.

[0038] The battery performance tests in the following embodiments all adopted the Xinwei battery testing system. In order to measure the long cycle time of the symmetrical battery, two polished zinc foils were used as two electrode sheets, and the electrolyte prepared in the following embodiment was used, and the glass fiber was used as a diaphragm to assemble a 2032 button pair battery, which was tested at a constant current density and constant time. In order to measure the coulombic efficiency of the battery, copper foil and zinc foil were used as positive and negative electrodes, respectively, and the electrolyte prepared in the following embodiment was used, and the glass fiber was used as a diaphragm to assemble a 2032 button battery, which was tested at a given current density and deposition time. In order to study the feasibility of the application of additives in actual full batteries, manganese dioxide (MnO 2 ) positive electrode material, Ketjen black and polyvinylidene fluoride (PVDF) were mixed and uniformly dissolved in N-methylpyrrolidone (NMP) solution in a mass ratio of 70:20:10 to prepare a slurry, which was then uniformly coated on carbon paper to prepare a working electrode. The electrolyte prepared in the following embodiment was used, and glass fiber was used as a separator to assemble a 2032 button cell. The test voltage range was 0.8V-1.8V vs. Zn / Zn 2+ .

[0039] Embodiment 1:

[0040] Step 1: Weigh 2.876 g of zinc sulfate hexahydrate (ZnSO 4 7H 2 O) was dissolved in 5 mL of deionized water. After they were completely dissolved, 0.023 g and 0.069 g of sodium tartrate (TA-Na) were weighed and added to the zinc sulfate solution, stirring while adding. After both were completely dissolved, they were stirred for 8 h under a magnetic stirrer using a magnet to mix the two evenly;

[0041] Step 2: The solution obtained by sufficient stirring is filtered by suction through a microporous filter membrane to remove insoluble impurities.

[0042] Embodiment 2:

[0043] Step 1: Weigh 2.876 g of zinc sulfate hexahydrate (ZnSO 4 7H 2 O) was dissolved in 5 mL of deionized water. After they were completely dissolved, 0.030 g and 0.089 g of sodium citrate (CA-Na) were weighed and added to the zinc sulfate solution, stirring while adding. After both were completely dissolved, a magnetic stirrer was used to stir for 8 h to mix the two evenly;

[0044] Step 2: The solution obtained by sufficient stirring is filtered by suction through a microporous filter membrane to remove insoluble impurities.

[0045] Figure 1 The long cycle diagram of the symmetrical zinc battery using the electrolyte containing different concentrations of sodium tartrate additive in Example 1. It can be seen from the figure that the cycle time of the battery is significantly increased after adding the sodium tartrate additive relative to the cycle life of the battery without the additive. The cycle life of the battery containing 0.01 mol / L sodium tartrate additive is extended to 1400 h. However, as the concentration of organic salt increases, the cycle life of the symmetrical zinc battery decreases, but it is still higher than that of the battery without the additive.

[0046] Figure 2 The long cycle diagram of the symmetrical zinc battery using the electrolyte containing different concentrations of sodium citrate additive in Example 2. It can be seen from the figure that the cycle time of the battery is significantly increased after adding the sodium citrate additive relative to the cycle life of the battery without the additive. The cycle life of the battery containing 0.01 mol / L sodium citrate additive is extended to 700 h. However, as the concentration of organic salt increases, the cycle life of the symmetrical zinc battery decreases, but it is still higher than that of the battery without the additive.

[0047] Figure 3 The coulomb efficiency comparison diagram of Zn-Cu battery using electrolyte containing different concentrations of sodium tartrate additive in Example 1. It can be seen from the figure that after adding sodium tartrate, Zn 2+ The reversibility of insertion and extraction is enhanced, and the coulombic efficiency is greater than 99%. Considering the influence of different concentrations of organic salt additives on the cycle time and coulombic efficiency of the battery, we believe that the electrolyte containing 0.01 mol / L sodium tartrate additive can maximize the performance improvement of the battery.

[0048] Figure 4 The coulombic efficiency comparison diagram of Zn-Cu battery using electrolyte containing different concentrations of sodium citrate additive in Example 2. It can be seen from the figure that after adding sodium citrate, Zn 2+ The reversibility of insertion and extraction is enhanced, and the coulombic efficiency is greater than 99%. Considering the effect of different concentrations of sodium citrate additives on the cycle time and coulombic efficiency of the battery, we believe that the electrolyte with 0.01 mol / L sodium citrate additive can maximize the performance of the battery.

[0049] Figure 5 The XRD comparison diagram of zinc foil after battery cycling using the electrolyte containing the optimal concentration (0.01 mol / L) of sodium tartrate and sodium citrate additives in Example 1 and Example 2 and the electrolyte without additives. 2 After 20 cycles, the zinc foil after the battery with organic salt added had a byproduct of Zn4 SO 4 (OH) 6 ·XH 2 The peak of O was significantly reduced. This shows that the organic salt additive inhibits the generation of by-products in the battery, and the inhibitory effect of 0.01 mol / L sodium tartrate additive is better than that of the corresponding sodium citrate.

[0050] Figure 6 , Figure 7 and Figure 8 The following are scans of the zinc foil after cycling using the electrolyte battery without organic salt additives and with the optimal concentration (0.01 mol / L) of sodium tartrate and sodium citrate additives in Example 1 and Example 2, respectively. The zinc foil after cycling without organic salt additives at a current density of 0.5 mAh / cm 2 After 20 cycles, zinc ions were deposited unevenly on the zinc surface, accompanied by large areas of zinc dendrites. Hexagonal flaky byproducts can be clearly seen on the surface of zinc foil. On the contrary, after adding organic salt additives, zinc ions were deposited evenly on the zinc surface, and the surface of zinc foil was relatively uniform and smooth. This shows that organic salt additives inhibited dendrite growth and the generation of byproducts.

[0051] Fig. 9 The XRD comparison diagrams of zinc foil immersed in the electrolyte containing the optimal concentration (0.01 mol / L) of sodium tartrate and sodium citrate additives in Example 1 and Example 2 and the electrolyte without additives for 7 days are shown in the figure. It is obvious from the figure that the zinc foil immersed in the electrolyte without organic salt has a byproduct Zn 4 SO 4 (OH) 6 The peak of xH2O is very high. Since the (002) crystal plane of zinc has the lowest surface energy in metallic zinc and the interfacial charge density is more uniform and smooth than that of the (100) crystal plane, the greater the ratio of the intensity of the diffraction peak of the Zn (002) crystal plane to the intensity of the diffraction peak of the Zn (100) crystal plane, the smoother the zinc deposition. This also means that organic salts will preferentially adsorb on the zinc surface, improve the interface environment between the zinc negative electrode and the electrolyte, and thus inhibit the occurrence of side reactions such as dendrites and corrosion.

[0052] Fig.10 , Fig.11 , Fig.12The scanned images are respectively of zinc foil immersed in the electrolyte without additives and the electrolyte containing the optimal concentration (0.01 mol / L) of sodium tartrate and sodium citrate additives in Example 1 and Example 2 for 7 days. It can be seen from the figure that after the zinc sheet was immersed in the electrolyte without organic salt additives for 7 days, a large number of dendrites grew on the surface of the zinc sheet, and a large number of hexagonal flaky by-products were accumulated. Similarly, the electrolyte without organic salt additives also corroded the surface of the zinc sheet. After adding the organic salt additive, whether it is sodium tartrate or sodium citrate, the surface of the zinc sheet immersed therein is still smooth and intact, and the corrosion ability of the electrolyte containing organic salts on the zinc sheet is reduced. It is said that the addition of organic salt additives inhibits the occurrence of side reactions such as dendrites and corrosion.

[0053] Fig.13 and Fig.14 The figures are rate performance comparisons of aqueous zinc ion batteries containing electrolytes with optimal concentrations (0.01 mol / L) of sodium tartrate and sodium citrate additives and no additives in Example 1 and Example 2. It can be seen from the figure that the specific capacity of aqueous zinc ion batteries using electrolytes containing organic salt additives at different current densities is significantly higher than that of aqueous zinc ion batteries using electrolytes without additives, indicating that batteries using electrolytes containing the additives have excellent rate performance.

[0054] Fig.15 and Fig.16 The following are the cycling performance comparisons of aqueous zinc ion batteries at a current density of 4A / g for electrolytes containing sodium tartrate and sodium citrate additives at optimal concentrations (0.01 mol / L) in Examples 1 and 2 and electrolytes without additives. The battery without organic salt additives failed completely due to severe capacity decay after about 3000 cycles. After adding organic salt additives, the Zn-MnO 2 The cycle performance of the battery is greatly improved. The addition of sodium citrate extends the cycle life of the Zn-MnO2 battery to 12,000 cycles. The addition of sodium tartrate additives 2 The cycle life of the battery was extended to 20,000 cycles. Although the effect of sodium citrate additive may not be as good as that of sodium tartrate, the addition of both greatly improved the cycle life of aqueous zinc ion batteries compared to batteries without organic salt additives.

[0055] In summary, the organic salt electrolyte additive prepared by the present invention can protect the zinc negative electrode, inhibit side reactions such as dendrites and corrosion, extend the service life of the aqueous zinc ion battery, and improve the cycle stability of the battery when applied to the aqueous zinc ion battery electrolyte. This is of great significance for the scale-up of aqueous zinc ion batteries.

Claims

1. An application of an aqueous zinc ion battery electrolyte capable of inhibiting side reactions such as dendrites and corrosion, characterized in that: An aqueous zinc ion battery is constructed using the aqueous zinc ion battery electrolyte; the aqueous zinc ion battery comprises a positive electrode, a negative electrode, a separator and the aqueous zinc ion battery electrolyte; The aqueous zinc ion battery electrolyte comprises zinc salt, deionized water and an organic salt additive; the zinc salt is zinc sulfate; the organic salt additive is sodium tartrate or sodium citrate; First, zinc sulfate particles are dissolved in deionized water, and then an organic salt additive is added to the zinc sulfate solution. Finally, the solution is fully mixed by stirring to obtain a zinc sulfate electrolyte containing an organic salt additive, and the concentration of the organic salt additive is 0.01-0.03 mol / L.

2. The use according to claim 1, characterized in that: Weigh 2.876 g~2.880 g zinc sulfate into a beaker, add a little deionized water to dissolve; then weigh the organic salt additive particles into the beaker, add deionized water to the 10 mL mark, stir while adding to completely dissolve the particles; after dissolution, continue stirring to mix evenly; use a microporous filter membrane to absorb the solution obtained by thorough stirring and filter the aqueous solution to remove insoluble impurities.

Citation Information

Patent Citations

  • Cathode and electrolyte of aqueous solution lithium ion secondary battery, and battery

    CN106207253A

  • Method for inhibiting growth of zinc dendrites in zinc ion battery / capacitor

    CN113299869A

Cited By

  • Mixed high-entropy electrolyte based on sodium citrate and sodium potassium tartrate tetrahydrate as well as preparation method and application of mixed high-entropy electrolyte

    CN121812778A